Кинетика процесса восстановления вольфрама из вольфрамовой кислоты H2WO4 в закрытом реакторе - Бондаренко, В.П.; Андреев, И.В.; Бабенко, А.Е. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The kinetic analysis of process of reduction of tungsten from H₂WO₄ in the closed reactor is carried out. It is shown, that application H₂WO₄ allows to raise homogeneity of process that speaks reduction E-activation.